Engineering the Multienzymatic Activity of Cerium Oxide Nanoparticle Coatings for the Antioxidant Protection of Implants. Issue 8 (21st May 2021) - Abuid, Nicholas J.; Urdaneta, Morgan E.; Gattas-Asfura, Kerim M.; Zientek, Caterina; Isusi Silgo, Cristina; Torres, Jose A.; Otto, Kevin J.; Stabler, Cherie L.
Abstract : Imbalance of oxidants is a universal contributor to the failure of implanted devices and tissues. A sustained oxidative environment leads to cytotoxicity, prolonged inflammation, and ultimately host rejection of implanted devices/grafts. The incorporation of antioxidant materials can inhibit this redox/inflammatory cycle and enhance implant efficacy. Cerium oxide nanoparticle (CONP) is a highly promising agent that exhibits potent, ubiquitous, and self‐renewable antioxidant properties. Integrating CONP as surface coatings provides ease in translating antioxidant properties to various implants/grafts. Herein, the formation of CONP coatings, generated via the sequential deposition of CONP and alginate, and the impact of coating properties, pH, and polymer molecular weight, on their resulting redox profile are described. Investigation of CONP deposition, layer formation, and coating uniformity/thickness on their resulting oxidant scavenging activity identify key parameters for customizing global antioxidant properties. Results found lower molecular weight alginates and physiological pH shift CONP activity to a higher H2 O2 to O2 − ‐scavenging capability. The antioxidant properties measured for these various coatings translate to distinct antioxidant protection to the underlying encapsulated cells. Information gained from this work can be leveraged to tailor coatings toward specific oxidant‐scavenging applications and prolong the function of medical devices and cellular implants. Abstract : Functionalization of biomaterials with a nanoscale antioxidant coating can be achieved using LbL technique, which incorporates cerium oxide nanoparticles (CONP) and alginate. The redox activity of the coatings can be manipulated by altering factors such as pH of CONP and the molecular weight of alginate. Herein, an array of coating formulations with variable H2 O2 /O2 − ‐scavenging capabilities is presented.